Hostname: page-component-745bb68f8f-lrblm Total loading time: 0 Render date: 2025-02-07T01:23:11.188Z Has data issue: false hasContentIssue false

APPLICATIONS OF CIRCULANT MATRICES TO DETERMINANTS INVOLVING $\boldsymbol {k}$TH POWER RESIDUES

Published online by Cambridge University Press:  09 February 2022

HAI-LIANG WU
Affiliation:
School of Science, Nanjing University of Posts and Telecommunications, Nanjing 210023, PR China e-mail: whl.math@smail.nju.edu.cn
LI-YUAN WANG*
Affiliation:
School of Physical and Mathematical Sciences, Nanjing Tech University, Nanjing 211816, PR China
Rights & Permissions [Opens in a new window]

Abstract

We use circulant matrices and hyperelliptic curves over finite fields to study some arithmetic properties of certain determinants involving Legendre symbols and kth power residues.

Type
Research Article
Copyright
© The Author(s), 2022. Published by Cambridge University Press on behalf of Australian Mathematical Publishing Association Inc.

1 Introduction

Let n be an arbitrary positive integer and let R be a commutative ring. For every $n\times n$ matrix $M=[a_{ij}]_{1\le i,j\le n}$ with $a_{ij}\in R$ , we use the symbol $\det M$ or $|M|$ to denote the determinant of M. Given any elements $b_0,b_1,\ldots ,b_{n-1}\in R$ , the circulant matrix of the n-tuple $(b_0,\ldots ,b_{n-1})$ is the $n\times n$ matrix over R whose $(i,j)$ -entry is $b_{i-j}$ , where the indices are cyclic modulo n. We also denote this matrix by $C(b_0,b_1,\ldots ,b_{n-1})$ . Circulant matrices have many applications in both number theory and combinatorics. We refer to the survey paper [Reference Kra and Simanca5] for results on circulant matrices.

1.1 Circulant matrices involving Legendre symbols

Let p be an odd prime and let $\, \chi (\cdot )$ be a multiplicative character modulo p. Carlitz [Reference Carlitz2] investigated the circulant matrix

$$ \begin{align*} C(c_0,c_1,\ldots,c_{p-1}):=[\mu+\, \chi(i-j)]_{1\le i,j\le p-1}\quad (\mu\in\mathbb{C}), \end{align*} $$

where $c_i=\mu +\, \chi (i)$ for $0\le i\le p-1$ . Carlitz [Reference Carlitz2, Theorem 4] determined the characteristic polynomial of this circulant matrix. In particular, when $\, \chi (\cdot )=\big(\frac{\cdot}{p}\big)$ is the Legendre symbol, the characteristic polynomial of the matrix $[\mu +({(i-j)}/{p})]_{1\le i,j\le p-1}$ is

$$ \begin{align*} F_{\mu}(t)=(t^2-(-1)^{(p-1)/2}p)^{(p-3)/2}(t^2-(p-1)\mu-(-1)^{(p-1)/2}). \end{align*} $$

Later, Chapman [Reference Chapman3, Reference Chapman4] and Vsemirnov [Reference Vsemirnov10, Reference Vsemirnov11] studied variants of Carlitz’s results.

Let $p=2n+1$ be an odd prime. Recently, Sun [Reference Sun9] studied the determinant

$$ \begin{align*} S(d,p):=\det\bigg[\bigg(\frac{i^2+dj^2}{p}\bigg)\bigg]_{1\le i,j\le n}, \end{align*} $$

where $\big(\frac{\cdot}{p}\big)$ is the Legendre symbol and $d\in \mathbb {Z}$ with $p\nmid d$ . Sun [Reference Sun9, Theorems 1.2(iii) and 1.3(i)] proved that $-S(d,p)$ is a quadratic residue modulo p whenever $\big(\frac{d}{p}\big)=1$ . (See [Reference Krachun, Petrov, Sun and Vsemirnov6, Reference Wu13] for recent progress on this topic.) Sun also investigated some global properties of this determinant and conjectured that $-S(1,p)$ is an integral square if $p\equiv 3\ ({\textrm {mod}}\ 4)$ . Later, by using a sophisticated matrix decomposition, Alekseyev and Krachun proved this conjecture. In the case $p\equiv 1\ ({\textrm {mod}}\ 4)$ , writing $p=a^2+4b^2$ with $a,b\in \Bbb Z$ and $a\equiv 1\ ({\textrm {mod}}\ 4)$ , Cohen, Sun and Vsemirnov conjectured that $S(1,p)/a$ is an integral square (see [Reference Sun9, Remark 4.2]). This conjecture was later proved by the first author [Reference Wu12, Theorem 3].

Note that $S(d,p)$ is indeed a determinant of a certain circulant matrix. In fact, fix a primitive root g modulo p. Then it is clear that $S(d,p)$ is equal to

$$ \begin{align*} \det\bigg[\bigg(\frac{g^{2i}+dg^{2j}}{p}\bigg)\bigg]_{0\le i,j\le n-1} =\det\bigg[\bigg(\frac{g^{2(i-j)}+d}{p}\bigg)\bigg]_{0\le i,j\le n-1} =\det C(s_0,s_1,\ldots,s_{n-1}), \end{align*} $$

where $s_i=({(g^{2i}+d)}/{p})$ for $0\le i\le n-1$ .

Motivated by Sun’s determinant $S(d,p)$ , we study some determinants containing kth power residues. Let p be an odd prime and let $k\ge 2$ be an integer dividing $p-1$ . Write $p=km+1$ and let

$$ \begin{align*} 0<\alpha_1<\alpha_2<\cdots<\alpha_m<p \end{align*} $$

be all the kth power residues modulo p in the interval $(0,p)$ . We consider the matrix

$$ \begin{align*} W_p(k):=\bigg[\bigg(\frac{\alpha_i+\alpha_j}{p}\bigg)\bigg]_{1\le i,j\le m}. \end{align*} $$

To state our results, we first introduce some notation. Let $\mathbb {F}_p$ denote the finite field of p elements. Let $\mathcal {C}_{p,k,\psi }$ and $\mathcal {C}_{p,k,\phi }$ be the curves over $\mathbb {F}_p$ defined by the equations $y^2=x^k+1$ and $y^2=x(x^k+1)$ , respectively. Define $a_p(k)$ and $b_p(k)$ by

(1.1) $$ \begin{align} p+1-a_p(k)=\text{\#}\{(x,y)\in\mathbb{F}_p\times\mathbb{F}_p:\ y^2=x^k+1\}\cup\{\infty\}, \end{align} $$

and

(1.2) $$ \begin{align} p+1-b_p(k)=\text{\#}\{(x,y)\in\mathbb{F}_p\times\mathbb{F}_p:\ y^2=x(x^k+1)\}\cup\{\infty\}, \end{align} $$

where $\infty $ denotes the point at infinity and $\#S$ denotes the cardinality of a set S.

When k is even, the following result generalises Sun’s determinant $S(1,p)$ .

Theorem 1.1. Let p be an odd prime and let $k\ge 2$ be an even integer dividing $p-1$ . Let $m=(p-1)/k$ .

  1. (i) If m is odd, then $\det W_p(k)=-(a_p(k)+1)u_p(k)^2/k$ for some $u_p(k)\in \mathbb {Z}$ .

  2. (ii) If m is even, then $ \det W_p(k)=(a_p(k)+1)b_p(k)v_p(k)^2/k^2 $ for some $v_p(k)\in \mathbb {Z}$ .

Remark 1.2. (1) When $k=2$ and $p\equiv 3\ ({\textrm {mod}}\ 4)$ , it is easy to see that $a_p(2)=1$ . This implies that $-\det W_p(2)=-S(1,p)$ is an integral square, which also confirms the conjecture of Sun.

(2) When $k=2$ and $p\equiv 1\ ({\textrm {mod}}\ 4)$ with $p=a^2+4b^2$ , where $a\equiv 1\ ({\textrm {mod}}\ 4)$ , it is known that $a_p(2)=1$ and $b_p(2)=2a$ [Reference Berndt, Evans and Williams1, Theorem 6.2.9]. Thus, $\det W_p(2)/a=S(1,p)/a$ is an integral square, which coincides with the result in [Reference Wu12, Theorem 3].

Now we consider the case when k is odd. Fix a primitive root g modulo p. Let $E_{p,k,1}$ and $E_{p,k,g}$ be the hyperelliptic curves over $\mathbb {F}_p$ defined by the equations $y^2=x(x^{2k}+1)$ and $y^2=x(x^{2k}+g^k)$ , respectively. Define $c_p(k)$ and $d_p(k)$ by

(1.3) $$ \begin{align} p+1-c_p(k):=\text{\#}\{(x,y)\in\mathbb{F}_p\times\mathbb{F}_p:\ y^2=x(x^{2k}+1)\}\cup\{\infty\}, \end{align} $$

and

(1.4) $$ \begin{align} p+1-d_p(k):=\text{\#}\{(x,y)\in\mathbb{F}_p\times\mathbb{F}_p:\ y^2=x(x^{2k}+g^k)\}\cup\{\infty\}. \end{align} $$

Theorem 1.3.

  1. (i) Let $p\equiv 1\ ({\mathrm {mod}}\ 4)$ be a prime and let $k\ge 3$ be an odd integer dividing $p-1$ . Then,

    $$ \begin{align*}\det W_p(k)=\frac{z_p(k)^2}{4k^2}(c_p(k)^2+d_p(k)^2) \end{align*} $$
    for some $z_p(k)\in \mathbb {Z}$ .
  2. (ii) Let $p\equiv 3\ ({\mathrm {mod}}\ 4)$ be a prime and let $k\ge 2$ be an odd integer dividing $p-1$ . Then, $-\det W_p(k)$ is an integral square.

When $k=3$ , we deduce the following consequence.

Corollary 1.4. Suppose that $p\equiv 1\ ({\mathrm {mod}}\ 12)$ is a prime and write $p=c^2+9d^2$ with $c,d\in \mathbb {Z}$ . Then

  1. (i) $\det W_p(3)/(c^2+d^2)$ is an integral square.

  2. (ii) Moreover, if $p\nmid \det W_p(3)$ , then

$$ \begin{align*}\bigg(\frac{\det W_p(3)}{p}\bigg)=\bigg(\frac{2}{p}\bigg). \end{align*} $$

Remark 1.5. There are primes $p\equiv 1\ ({\textrm {mod}}\ 12)$ such that $p\mid \det W_p(3)$ . In fact, $1117,1129,1381,1597,1861,2557,2749$ are all the primes $p\equiv 1\ ({\textrm {mod}}\ 12)$ less than $3000$ such that $p\mid W_p(3)$ .

Corollary 1.6.

  1. (i) Let $p\equiv 1\ ({\mathrm {mod}}\ 4)$ be a prime and let $k\ge 2$ be an odd integer dividing $p-1$ . Then, $\det W_p(k)\ge 0$ .

  2. (ii) Let $p\equiv 3\ ({\mathrm {mod}}\ 4)$ be a prime and let $k\ge 2$ be an odd integer dividing $p-1$ . Then, $\det W_p(k)\le 0$ .

1.2 Determinants of the form $\textbf {det}[{1}/{(\alpha _i+\alpha _j)}]_{1\le i,j\le m}$

Let p be an odd prime. For any integer t with $p\nmid t$ , the element $1/t$ mod p denotes the multiplicative inverse of t mod p. In 2019, Sun [Reference Sun9] also studied the determinant

$$ \begin{align*}A_p:=\det\bigg[\frac{1}{i^2+j^2}\bigg]_{1\le i,j\le (p-1)/2}. \end{align*} $$

When $p\equiv 3\ ({\textrm {mod}}\ 4)$ , Sun [Reference Sun9, Theorem 1.4(ii)] showed that

$$ \begin{align*}A_p\equiv \bigg(\frac{2}{p}\bigg)\ ({\textrm{mod}}\ p). \end{align*} $$

In [Reference Sun9, Remark 1.3], Sun also conjectured that if $p\equiv 2\ ({\textrm {mod}}\ 3)$ is odd, then $2B_p$ is a quadratic residue modulo p, where

$$ \begin{align*}B_p:=\det\bigg[\frac{1}{i^2-ij+j^2}\bigg]_{1\le i,j\le p-1}. \end{align*} $$

This conjecture was later confirmed in [Reference Wu, She and Ni14]. With the notation established in the previous subsection, we consider the matrix

$$ \begin{align*} I_p(k):=\bigg[\frac{1}{\alpha_i+\alpha_j}\bigg]_{1\le i,j\le m}. \end{align*} $$

As a generalisation of Sun’s determinant $\det A_p$ , we obtain the following result.

Theorem 1.7. Let p be an odd prime and let $k\ge 2$ be an even integer dividing $p-1$ . Write $p=km+1$ . Suppose that $-1$ is not a kth power residue modulo p. Then

$$ \begin{align*}\det I_p(k)\equiv \frac{(-1)^{{m+1}/{2}}}{(2k)^m}\ ({\mathrm{mod}}\ p). \end{align*} $$

Remark 1.8. When $p\equiv 3\ ({\textrm {mod}}\ 4)$ and $k=2$ , the theorem gives

$$ \begin{align*}\det I_p(2)\equiv (-1)^{{p+1}/{4}}=\bigg(\frac{2}{p}\bigg)\ ({\textrm{mod}}\ p). \end{align*} $$

This coincides with Sun’s result [Reference Sun9, Theorem 1.4(ii)].

The outline of the paper is as follows. We will prove Theorems 1.11.3 and their corollaries in Section 2. The proof of Theorem 1.7 will be given in Section 3.

2 Proofs of Theorems 1.1–1.3

Recall that $C(a_0,\ldots ,a_{n-1})$ denotes the circulant matrix of the n-tuple $(a_0,\ldots ,a_{n-1})$ . The following lemma is Lemma 3.4 of [Reference Wu13] and is the key element of our proofs.

Lemma 2.1. Let R be a commutative ring, n a positive integer and $a_0,a_1,\ldots ,a_{n-1}\in R$ such that

(2.1) $$ \begin{align} a_i=a_{n-i}\quad \text{for}\ 1\le i\le n-1. \end{align} $$

If n is even, then there exists an element $u\in R$ such that

$$ \begin{align*} \det C(a_0,a_1,\ldots,a_{n-1})=\bigg(\sum_{i=0}^{n-1}a_i\bigg) \bigg(\sum_{i=0}^{n-1}(-1)^ia_i\bigg) u^2. \end{align*} $$

If n is odd, then there exists an element $v\in R$ such that

$$ \begin{align*} \det C(a_0,a_1,\ldots,a_{n-1})=\bigg(\sum_{i=0}^{n-1}a_i\bigg) v^2. \end{align*} $$

Proof of Theorem 1.1.

Fix a primitive root g modulo p. As k is even,

$$ \begin{align*} \det W_p(k) & =\det\bigg[\bigg(\frac{1+\alpha_i/\alpha_j}{p}\bigg)\bigg]_{1\le i,j\le m} =\det\bigg[\bigg(\frac{1+g^{k(i-j)}}{p}\bigg)\bigg]_{0\le i,j\le m-1}\\ &=\det C(e_0,e_1,\ldots,e_{m-1}), \quad\mbox{where } e_i=\bigg(\frac{1+g^{ki}}{p}\bigg)\ \mbox{for } 0\le i\le m-1. \end{align*} $$

Clearly $e_0,\ldots ,e_{m-1}$ satisfy the condition (2.1). Moreover,

(2.2) $$ \begin{align} \sum_{i=0}^{m-1}e_i =\frac{1}{k}\sum_{x=1}^{p-1}\bigg(\frac{1+x^k}{p}\bigg) =\frac{1}{k}\bigg(-1+\sum_{x=0}^{p-1}\bigg(\frac{1+x^k}{p}\bigg)\bigg) =-\frac{1+a_p(k)}{k}, \end{align} $$

where $a_p(k)$ is defined by (1.1). Also,

(2.3) $$ \begin{align} \sum_{i=0}^{m-2}(-1)^ie_i=\frac{1}{k}\sum_{x=1}^{p-1}\bigg(\frac{x^k+1}{p}\bigg)\bigg(\frac{x}{p}\bigg) =-\frac{b_p(k)}{k}, \end{align} $$

where $b_p(k)$ is defined by (1.2). Combining Lemma 2.1 with (2.2) and (2.3) yields the desired result.

Now we turn to the proof of Theorem 1.3. We first need the following well-known result in linear algebra.

Lemma 2.2. Let M be an $n\times n$ complex matrix. Let $\lambda _1,\ldots ,\lambda _n$ be complex numbers and let $\mathbf {u}_1,\ldots , \mathbf {u}_n$ be m-dimensional column vectors. Suppose that $M\mathbf {u}_i=\lambda _i\mathbf {u}_i$ for $1\le i\le n$ and that $\mathbf {u}_1,\ldots , \mathbf {u}_n$ are linearly independent. Then $\lambda _1,\ldots ,\lambda _n$ are exactly all the eigenvalues of M (counting multiplicities).

Let $\widehat {\mathbb {F}_p^{\times }}$ denote the cyclic group of all multiplicative characters of $\mathbb {F}_p$ and let $\, \chi _p(\cdot )$ be a generator of $\widehat {\mathbb {F}_p^{\times }}$ . For any matrix M, we use the symbol $M^T$ to denote the transpose of M.

Proof of Theorem 1.3.

Recall that $k\ge 2$ is an odd integer dividing $p-1$ and $p=km+1$ .

(i) We first consider the case $p\equiv 1\ ({\textrm {mod}}\ 4)$ . Clearly, the elements $\alpha _1\ \textrm {mod}\ p ,\ldots , \alpha _m \textrm { mod}\ p$ are exactly m distinct roots of the polynomial $X^m-1$ over $\mathbb {F}_p=\mathbb {Z}/p\mathbb {Z}$ . Therefore,

(2.4) $$ \begin{align} X^m-1\equiv \prod_{i=1}^{m}(X-\alpha_i)\ ({\textrm{mod}}\ p). \end{align} $$

By (2.4),

(2.5) $$ \begin{align} \prod_{j=1}^m\alpha_j\equiv -1^{m+1}=-1\ ({\textrm{mod}}\ p). \end{align} $$

By (2.5), it is easy to see that $\det W_p(k)$ is equal to

$$ \begin{align*} \bigg(\frac{-1}{p}\bigg) \det\bigg[\bigg(\frac{\alpha_i+\alpha_j}{p}\bigg)\bigg]_{1\le i,j\le m} =\det\bigg[\bigg(\frac{\alpha_i+\alpha_j}{p}\bigg)\bigg(\frac{\alpha_j}{p}\bigg)\bigg]_{1\le i,j\le m}. \end{align*} $$

Next, we determine all the eigenvalues of the matrix

$$ \begin{align*}W^*_p(k):=\bigg[\bigg(\frac{\alpha_i+\alpha_j}{p}\bigg)\bigg(\frac{\alpha_j}{p}\bigg)\bigg]_{1\le i,j\le m}. \end{align*} $$

For each r with $1\le r\le m$ ,

$$ \begin{align*} \sum_{j=1}^{m}\bigg(\frac{\alpha_i+\alpha_j}{p}\bigg)\bigg(\frac{\alpha_j}{p}\bigg)\,\, \chi_p^r(\alpha_j) &=\sum_{j=1}^{m}\bigg(\frac{1+\alpha_j/\alpha_i}{p}\bigg)\bigg(\frac{\alpha_j/\alpha_i}{p}\bigg)\, \, \chi_p(\alpha_j/\alpha_i)\,\, \chi_p^r(\alpha_i)\\ &=\sum_{j=1}^{m}\bigg(\frac{1+\alpha_j}{p}\bigg)\bigg(\frac{\alpha_j}{p}\bigg) \,\, \chi_p^r(\alpha_j)\,\, \chi_p^r(\alpha_i). \end{align*} $$

This implies that for $1\le r\le m$ ,

$$ \begin{align*}W^*_p(k)\mathbf{v}_r=\lambda_r\mathbf{v}_r, \end{align*} $$

where

$$ \begin{align*}\lambda_r=\sum_{j=1}^{m}\bigg(\frac{1+\alpha_j}{p}\bigg)\bigg(\frac{\alpha_j}{p}\bigg) \, \chi_p^r(\alpha_j) \quad\mbox{and}\quad \mathbf{v}_r=(\, \chi_p^r(\alpha_1),\ldots,\, \chi_p^r(\alpha_m))^T. \end{align*} $$

Note that

$$ \begin{align*}\left| \begin{array}{cccccccc} \, \chi_p^1(\alpha_1) & \, \chi_p^2(\alpha_1) & \ldots & \, \chi_p^m(\alpha_1) \\ \, \chi_p^1(\alpha_2) & \, \chi_p^2(\alpha_2) & \ldots & \, \chi_p^n(\alpha_2)\\ \vdots & \vdots & \ddots & \vdots \\ \, \chi_p^1(\alpha_n)& \, \chi_p^2(\alpha_n) & \ldots & \, \chi_p^m(\alpha_m)\\ \end{array} \right| = \pm\prod_{1\le i<j\le m} (\, \chi_p(\alpha_j)-\, \chi_p(\alpha_i) )\ne0. \end{align*} $$

Hence, the vectors $\mathbf {v}_1,\ldots , \mathbf {v}_m$ are linearly independent. Now by Lemma 2.2, the numbers $\lambda _1,\ldots ,\lambda _m$ are exactly all the eigenvalues of $W^*_p(k)$ (counting multiplicities).

When $r=m$ ,

$$ \begin{align*} \lambda_m=\sum_{j=1}^m\bigg(\frac{1+\alpha_j}{p}\bigg)\bigg(\frac{\alpha_j}{p}\bigg) =\frac{1}{k}\sum_{x=1}^{p-1}\bigg(\frac{1+x^k}{p}\bigg)\bigg(\frac{x}{p}\bigg). \end{align*} $$

When $r=m/2$ ,

$$ \begin{align*} \lambda_{m/2}=\sum_{j=1}^m\bigg(\frac{1+\alpha_j}{p}\bigg) =\frac{1}{k}\sum_{x=1}^{p-1}\bigg(\frac{1+x^k}{p}\bigg). \end{align*} $$

By [Reference Berndt, Evans and Williams1, Proposition 6.1.7],

(2.6) $$ \begin{align} \lambda_m=\lambda_{m/2}. \end{align} $$

In addition, when $1\le r\le m/2-1$ , it is clear that $\overline {\lambda _r}=\lambda _{m-r}$ , where $\bar {z}$ denotes the complex conjugate of a complex number z. Combining this with (2.6),

(2.7) $$ \begin{align} \det W_p(k)=\det W^*_p(k)=\prod_{r=1}^m\lambda_r =\lambda_m^2\prod_{1\le r\le m/2-1}\lambda_r\overline{\lambda_r}\ge0. \end{align} $$

Let $\mathbf {i}\in \mathbb {C}$ be a primitive fourth root of unity. Fix a primitive root g modulo p. Then

$$ \begin{align*} \det W^*_p(k) &=\det\bigg[\bigg(\frac{\alpha_i+\alpha_j}{p}\bigg)\bigg(\frac{\alpha_j}{p}\bigg)\,\mathbf{i}^{i-j}\bigg]_{1\le i,j\le m}\\ &=\det\bigg[\bigg(\frac{1+g^{k(i-j)}}{p}\bigg)\,\mathbf{i}^{i-j}\bigg]_{0\le i,j\le m-1}\\ &=\det C(\omega_0,\ldots,\omega_{m-1}) \quad\mbox{where } \omega_r=\bigg(\frac{1+g^{kr}}{p}\bigg)\,\mathbf{i}^r \ \mbox{for } 0\le r\le m-1. \end{align*} $$

One can verify that $\omega _0,\ldots ,\omega _{m-1}$ satisfy the condition (2.1). Fix a multiplicative character $\psi \in \widehat {\mathbb {F}_p^{\times }}$ of order $4$ with $\psi (g)=\mathbf {i}$ . Then

$$ \begin{align*} \sum_{r=0}^{m-1}\omega_r =\sum_{r=0}^{m-1}\bigg(\frac{1+g^{kr}}{p}\bigg)\psi(g^r) =\frac{1}{k}\sum_{r=0}^{p-2}\bigg(\frac{1+g^{kr}}{p}\bigg)\psi(g^r). \end{align*} $$

One can also verify the following equalities:

$$ \begin{align*} \sum_{r=0}^{p-2}\bigg(\frac{1+g^{kr}}{p}\bigg)\psi(g^r) &=\sum_{r=0}^{{(p-3)}/{2}}\bigg(\frac{1+g^{2kr}}{p}\bigg)\bigg(\frac{g^r}{p}\bigg) +\mathbf{i}\sum_{r=0}^{({p-3})/{2}}\bigg(\frac{1+g^{2kr}g^k}{p}\bigg)\bigg(\frac{g^r}{p}\bigg)\\ &=\frac{1}{2}\sum_{x=1}^{p-1}\bigg(\frac{1+x^{2k}}{p}\bigg)\bigg(\frac{x}{p}\bigg) +\frac{1}{2}\mathbf{i}\sum_{x=1}^{p-1}\bigg(\frac{1+x^{2k}g^k}{p}\bigg)\bigg(\frac{x}{p}\bigg)\\ &=\frac{1}{2}\sum_{x=1}^{p-1}\bigg(\frac{1+x^{2k}}{p}\bigg)\bigg(\frac{x}{p}\bigg) +\frac{1}{2}\mathbf{i}\sum_{x=1}^{p-1}\bigg(\frac{g^k+x^{2k}}{p}\bigg)\bigg(\frac{x}{p}\bigg)\\ &=-\frac{c_p(k)+\mathbf{i}d_p(k)}{2}, \end{align*} $$

where $c_p(k)$ and $d_p(k)$ are defined by (1.3) and (1.4), respectively. Hence,

(2.8) $$ \begin{align} \sum_{r=0}^{m-1}\omega_r= - \frac{c_p(k)+\mathbf{i}d_p(k)}{2k}. \end{align} $$

With essentially the same method, one can also verify that

(2.9) $$ \begin{align} \sum_{r=0}^{m-1}(-1)^r\omega_r= - \frac{c_p(k)-\mathbf{i}d_p(k)}{2k}. \end{align} $$

If $\det W_p(k)=0$ , then one can get the desired result directly. Suppose now that $\det W_p(k)\ne 0$ . By (2.7), we have $\det W_p(k)>0$ under this assumption. Combining Lemma 2.1 with (2.8) and (2.9), there exists an element $z_p(k)\in \mathbb {Z}[\mathbf {i}]$ such that

$$ \begin{align*}\det W_p(k)=\det W_p^*(k)=\frac{z_p(k)^2}{4k^2}(c_p(k)^2+d_p(k)^2). \end{align*} $$

As $\det W_p(k)\in \mathbb {Z}$ and $\det W_p(k)>0$ , the number $z_p(k)$ must be an integer. This completes the proof of (i).

(ii) We now consider the case $p\equiv 3\ ({\textrm {mod}}\ 4)$ . As k is odd, it is clear that

$$ \begin{align*}-\alpha_1\ \textrm{mod}\ p,\ldots, -\alpha_{m}\ \textrm{mod}\ p \end{align*} $$

is a permutation $\pi $ of the sequence

$$ \begin{align*}\alpha_1\ \textrm{mod}\ p,\ldots, \alpha_{m}\ \textrm{mod}\ p, \end{align*} $$

and clearly

$$ \begin{align*}\textrm{sgn}(\pi)\equiv\prod_{1\le i<j\le m}\frac{-\alpha_j-(-\alpha_i)}{\alpha_j-\alpha_i}=(-1)^{m(m-1)/2}\ ({\textrm{mod}}\ p), \end{align*} $$

where $\textrm {sgn}(\pi )$ is the sign of $\pi $ . When $p\equiv 3\ ({\textrm {mod}}\ 4)$ and k is odd, since $m\equiv 2\ ({\textrm {mod}}\ 4)$ , the number $\det W_p(k)$ is equal to

$$ \begin{align*}\textrm{sgn}(\pi)\det\bigg[\bigg(\frac{\alpha_i-\alpha_j}{p}\bigg)\bigg]_{1\le i,j\le m} =-\det\bigg[\bigg(\frac{\alpha_i-\alpha_j}{p}\bigg)\bigg]_{1\le i,j\le m}. \end{align*} $$

Clearly, the matrix $M_p:=[({(\alpha _i-\alpha _j)}/{p})]_{1\le i,j\le m}$ is skew-symmetric, that is, $M_p^{T}=-M_p$ . The determinant of a skew-symmetric matrix of even order with integer entries is always an integral square (see [Reference Stembridge8, Proposition 2.2]). This implies that $-\det W_p(k)$ is an integral square.

This completes the proof.

Proof of Corollary 1.4.

(i) Let $k=3$ and $p\equiv 1\ ({\textrm {mod}}\ 12)$ . Write $p=\alpha ^2+\beta ^2$ with $\alpha ,\beta \in \mathbb {Z}$ and $\alpha \equiv -({2}/{p})\ ({\textrm {mod}}\ 4)$ . From [Reference Berndt, Evans and Williams1, Theorem 6.2.5],

$$ \begin{align*}c_p(3)^2=\begin{cases}36\alpha^2&\mbox{if}\ 3\nmid \alpha,\\ 4\alpha^2&\mbox{if}\ 3\mid\alpha,\end{cases},\quad d_p(3)^2=\begin{cases}4\beta^2&\mbox{if}\ 3\nmid \alpha,\\ 36\beta^2&\mbox{if}\ 3\mid\alpha.\end{cases} \end{align*} $$

Hence, if we write $p=c^2+9d^2$ with $c,d\in \Bbb Z$ , then one can easily verify that

$$ \begin{align*}\frac{c_p(3)^2+d_p(3)^2}{36}=c^2+d^2. \end{align*} $$

By Theorem 1.3, $\det W_p(3)/(c^2+d^2)$ is an integral square if $p\equiv 1\ ({\textrm {mod}}\ 12)$ .

(ii) If $p\nmid \det W_p(3)$ , then

$$ \begin{align*}\bigg(\frac{\det W_p(3)}{p}\bigg)=\bigg(\frac{c^2+d^2}{p}\bigg) =\bigg(\frac{8c^2+p}{p}\bigg)=\bigg(\frac{2}{p}\bigg). \end{align*} $$

This completes the proof.

3 Proof of Theorem 1.7

Recall that

$$ \begin{align*}I_p(k)=\bigg[\frac{1}{\alpha_i+\alpha_j}\bigg]_{1\le i,j\le m}. \end{align*} $$

As $-1$ is not a kth power residue modulo p, clearly we have $2\nmid m$ .

Proof of Theorem 1.7.

By [Reference Krattenthaler7, Theorem 12(5.5)],

$$ \begin{align*} \det I_p(k)=\frac{\prod_{1\le i<j\le m}(\alpha_i-\alpha_j)^2} {\prod_{1\le i\le m}\prod_{1\le j\le m}(\alpha_i+\alpha_j)}. \end{align*} $$

We first consider the numerator. One can verify the equalities

$$ \begin{align*} N_p:=\prod_{1\le i<j\le m}(\alpha_i-\alpha_j)^2 &=(-1)^{{m(m-1)}/{2}}\prod_{1\le i\ne j\le m}(\alpha_i-\alpha_j)\\[4pt] &=(-1)^{{(m-1)}/{2}}\prod_{1\le j\le m}\prod_{i\ne j}(\alpha_j-\alpha_i)\\[4pt] &=(-1)^{{(m-1)}/{2}}\prod_{1\le j\le m}G'(\alpha_j), \end{align*} $$

where $G'(X)$ is the derivative of $G(X)=\prod _{1\le i\le m}(X-\alpha _i)$ . Observe that

(3.1) $$ \begin{align} G(X)\equiv X^m-1\ ({\textrm{mod}}\ p). \end{align} $$

Hence, $G'(X)\equiv mX^{m-1}\ ({\textrm {mod}}\ p)$ and $\prod _{1\le i\le m}\alpha _i\equiv (-1)^{m+1}=1\ ({\textrm {mod}}\ p)$ . This gives

(3.2) $$ \begin{align} N_p = \prod_{1\le i<j\le m}(\alpha_i-\alpha_j)^2 &=(-1)^{{(m-1)}/{2}}\prod_{1\le j\le m}G'(\alpha_j) \nonumber\\[4pt] &\equiv (-1)^{{(m-1)}/{2}}m^m\prod_{1\le j\le m}\alpha_j^{m-1}\equiv (-1)^{{(m-1)}/{2}}m^m\ ({\textrm{mod}}\ p). \end{align} $$

Now we turn to the denominator. One can verify the equalities

$$ \begin{align*} D_p:=\prod_{i=1}^m\prod_{j=1}^m(\alpha_i+\alpha_j) & =\prod_{i=1}^m\alpha_i^m\prod_{j=1}^m(1+\alpha_j/\alpha_i) \\ & \equiv \prod_{i=1}^m\prod_{j=1}^m(1+\alpha_j) =\prod_{j=1}^m(1+\alpha_j)^m\ ({\textrm{mod}}\ p). \end{align*} $$

Hence, by (3.1),

(3.3) $$ \begin{align} D_p\equiv (-1)^mG(-1)^m\equiv 2^m\ ({\textrm{mod}}\ p). \end{align} $$

Combining (3.2) with (3.3), we finally obtain

$$ \begin{align*}\det I_p(k)\equiv \frac{(-1)^{(m-1)/{2}}m^m}{2^m}\equiv\frac{(-1)^{(m+1)/2}}{(2k)^m}\ ({\textrm{mod}}\ p). \end{align*} $$

This completes the proof.

Acknowledgement

We would like to thank the referee for helpful comments.

Footnotes

The first author was supported by the National Natural Science Foundation of China (Grant No. 12101321) and the Natural Science Foundation of the Higher Education Institutions of Jiangsu Province (Grant No. 21KJB110002). The second author was supported by the Natural Science Foundation of the Higher Education Institutions of Jiangsu Province (Grant No. 21KJB110001).

References

Berndt, B. C., Evans, R. J. and Williams, K. S., Gauss and Jacobi Sums (Wiley, New York, 1998).Google Scholar
Carlitz, L., ‘Some cyclotomic matrices’, Acta Arith. 5 (1959), 293308.CrossRefGoogle Scholar
Chapman, R., ‘Determinants of Legendre symbol matrices’, Acta Arith. 115 (2004), 231244.CrossRefGoogle Scholar
Chapman, R., ‘My evil determinant problem’, Preprint, 2012, available from http://empslocal.ex.ac.uk/people/staff/rjchapma/etc/evildet.pdf.Google Scholar
Kra, I. and Simanca, S. R., ‘On circulant matrices’, Notices Amer. Math. Soc. 59 (2012), 368377.CrossRefGoogle Scholar
Krachun, D., Petrov, F., Sun, Z.-W. and Vsemirnov, M., ‘On some determinants involving Jacobi symbols’, Finite Fields Appl. 64 (2020), 101672.CrossRefGoogle Scholar
Krattenthaler, C., ‘Advanced determinant calculus: a complement’, Linear Algebra Appl. 411 (2005), 68166.CrossRefGoogle Scholar
Stembridge, J. R., ‘Nonintersecting paths, pfaffians and plane partitions’, Adv. Math. 83 (1990), 96131.CrossRefGoogle Scholar
Sun, Z.-W., ‘On some determinants with Legendre symbol entries’, Finite Fields Appl. 56 (2019), 285307.CrossRefGoogle Scholar
Vsemirnov, M., ‘On the evaluation of R. Chapman’s “evil determinant”’, Linear Algebra Appl. 436 (2012), 41014106.CrossRefGoogle Scholar
Vsemirnov, M., ‘On R. Chapman’s “evil determinant”: case $p\equiv 1\left(\mathrm{mod}\ 4\right)$ ’, Acta Arith. 159 (2013), 331344.CrossRefGoogle Scholar
Wu, H.-L., ‘Determinants concerning Legendre symbols’, C. R. Math. Acad. Sci. Paris 359(6) (2021), 651655.Google Scholar
Wu, H.-L., ‘Elliptic curves over ${F}_p$ and determinants of Legendre matrices’, Finite Fields Appl. 76 (2021), 101929.CrossRefGoogle Scholar
Wu, H.-L., She, Y.-F. and Ni, H.-X., ‘Trinomial coefficients and a determinant of Sun’, Preprint, 2021, arXiv:2108.10624.Google Scholar